THE ROLE OF SELF-ESTEEM IN THE PERSONALITY DEVELOPMENT AND PROFESSIONAL SELF-DETERMINATION OF HIGH SCHOOL STUDENTS (Psychology Travelogs, 2025)
The article is devoted to the problem of personality development and professional self-determination of high school students. The purpose of the article is to study the role of self-esteem in personality development and professional self-determination of high school students. Based on the results of the review, the following conclusions were made: 1) self-esteem plays an important role in the development of the individual and the professional self-determination of high school students; it determines not only the perception and acceptance of a person of himself, but also has significance in the structure of the individual’s dignity, affects the individual’s motivational sphere, the development of the individual’s social intelligence, social adaptation and social behavior and affects the vital activity and quality of life of the individual; 2) during the study in the senior grades of school, a person develops the ability to adequately assess his personal capabilities regarding professional self-realization, therefore, the further development of the personality also depends on this stage of life, since a successfully chosen professional activity opens up powerful opportunities for a person to reveal and further develop his natural potential; 3) high school students with an adequate level of self-esteem are more prone to conscious professional self-determination, while in students with low self-esteem, professional self-determination is mainly imposed from the outside and is not the result of independent choice; high school students with inflated self-esteem have difficulties with professional self-determination, because a sense of self-sufficiency interferes with the realization of the personality; 4) there is a correlation between the level of self-esteem and the professional orientation of the personality and the type of profession with which a person most closely identifies.
Keywords: self-esteem; personality; development; professional self-determination; high school students